2016
DOI: 10.5812/hepatmon.33881
|View full text |Cite
|
Sign up to set email alerts
|

The Liver MicroRNA Expression Profiles Associated With Chronic Hepatitis C Virus (HCV) Genotype-4 Infection: A Preliminary Study

Abstract: BackgroundMicroRNAs (miRNAs) have been repeatedly shown to play important roles in liver pathologies, including hepatitis, liver cirrhosis, and liver cancer. Egypt has the highest hepatitis C virus (HCV) infection rate worldwide, predominantly involving genotype-4.ObjectivesIn this study, we attempted to characterize the miRNA profile of the poorly studied genotype 4 of HCV in chronically infected Egyptian patients to obtain a better understanding of the disease and its complications and help in the design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
2
28
3
Order By: Relevance
“…El‐Guendy et al have evaluated the miRNA expression profiles associated with chronic HCV genotype‐4 infection and found that miRNA‐21 showed downregulation with severe chronic hepatic inflammation.…”
Section: Discussioncontrasting
confidence: 99%
“…El‐Guendy et al have evaluated the miRNA expression profiles associated with chronic HCV genotype‐4 infection and found that miRNA‐21 showed downregulation with severe chronic hepatic inflammation.…”
Section: Discussioncontrasting
confidence: 99%
“…17 Numerous miRNAs have also engaged with the HCV genome decreasing its replication, inclusive miR-196, miR-199, and miR-448. 18 In addition, overexpression of miR-29 can inhibit viral RNA replication in HCV-infected patients. 19 However, the capability, the clinical value of circulating miRNAs for diagnosing and managing persistent hepatitis C has not been satisfactorily tested.…”
Section: Funding Informationmentioning
confidence: 99%
“…It was recognized as a positive regulatory factor for HCV replication by means of binding to two sites within the HCV genome . Numerous miRNAs have also engaged with the HCV genome decreasing its replication, inclusive miR‐196, miR‐199, and miR‐448 . In addition, overexpression of miR‐29 can inhibit viral RNA replication in HCV‐infected patients .…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al previously reported that miR-196b was notably upregulated in HCC compared with adjacent non-cancerous tissues (11). Furthermore, upregulation of miR-196b was found to be associated with HCV infection, suggesting a promoting role in HCC development (12). Yet, the clinical significance of miR-196b and its role as well as the underlying mechanisms remain largely unknown in HCC.…”
Section: Introductionmentioning
confidence: 99%